2021
DOI: 10.33558/jrak.v12i2.2682
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Company's Strategy and Characteristics of Earnings Quality

Abstract: This study aims to determine the effect of company strategy proxied by­ cost leadership strategy, differentiation strategy and investment opportunity set, and company characteristics proxied by company size, managerial ownership structure, institutional ownership structure and audit quality on earnings quality in manufacturing companies listed on the Indonesia Stock Exchange 2015-2019. The population in this study were 175 companies with a total sample size 37 compenies. The method used in determining the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…However, the results of this study contradict the research of Anam and Afrohah (2020), , Andriani et al (2021), Cahyani and Khafid (2020), Nariman and Ekadjaja (2018), Irawan and Ardianti (2021), Warianto and Rusiti (2014), Erawati and Rahmawati (2022), and Frengky (2019) who stated that firm size has a significant positive effect on earnings quality. As for the research from Saleh et al (2020) and Idhastari (2021) found a negative correlation.…”
Section: Best Model Selection Test Resultsmentioning
confidence: 73%
“…However, the results of this study contradict the research of Anam and Afrohah (2020), , Andriani et al (2021), Cahyani and Khafid (2020), Nariman and Ekadjaja (2018), Irawan and Ardianti (2021), Warianto and Rusiti (2014), Erawati and Rahmawati (2022), and Frengky (2019) who stated that firm size has a significant positive effect on earnings quality. As for the research from Saleh et al (2020) and Idhastari (2021) found a negative correlation.…”
Section: Best Model Selection Test Resultsmentioning
confidence: 73%